CANDi: context‐aware node discovery for short‐range cooperation1. Issue 5 (14th November 2013) - Alam, Muhammad; Albano, Michele; Radwan, Ayman; Rodriguez, Jonathan
Abstract: Multi‐standard mobile devices are allowing users to enjoy higher data rates with ubiquitous connectivity. However, the benefits gained from multiple interfaces come at an expense—that being higher energy consumption in an era where mobile devices need to be energy compliant. One promising solution is the usage of short‐range cooperative communication as an overlay for infrastructure‐based networks taking advantage of its context information. However, the node discovery mechanism, which is pivotal to the bearer establishment process, still represents a major burden in terms of the total energy budget. In this paper, we propose a technology agnostic approach towards enhancing the MAC energy ratings by presenting a context‐aware node discovery (CANDi) algorithm, which provides a priori knowledge towards the node discovery mechanism by allowing it to search nodes in the near vicinity at the 'right time and at the right place'. We describe the different beacons required for establishing the cooperation, as well as the context information required, including battery level, modes, location and so on. CANDi uses the long‐range network (WiMAX and WiFi) to distribute the context information about cooperative clusters (Ultra‐wideband‐based) in the vicinity. The searching nodes can use this context in locating the cooperative clusters/nodes, which facilitates the establishing of short‐range connections. Analytical and simulation results are obtained, and the energy saving gains are further demonstrated in the laboratory using a customised testbed. CANDi saves up to 50% energy during the node discovery process, while the demonstrative testbed shows up to 75% savings in the total energy budget, thus validating the algorithm, as well as providing viable evidence to support the usage of short‐range cooperative communications for energy savings. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We propose a technology agnostic approach towards enhancing the MAC energy ratings by presenting a context‐aware node discovery algorithm, which provides a priori knowledge towards the node discovery mechanism by allowing it to search nodes in the near vicinity at the 'right time and at the right place.' Analytical and simulation results are obtained, and the energy saving gains are further demonstrated in the laboratory using a customised testbed. Context‐aware node discovery algorithm saves up to 50% energy during node discovery process.